Legal and ethical basis of the interaction of provisors (doctors) with public control subjects of the quality assurance of medicines at the stages of their sale and medical use - L. H. Yurkovska; V. V. Krasnov; S. H. Ubohov (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Modern domestic public activism as a phenomenon that has become widespread relatively recently, creates new challenges for the pharmaceutical sector of the health care branch. Legal and ethical aspects of the interaction of pharmacists and doctors with public control subjects of the quality assurance of medicines remain insufficiently studied, which causes a lack of awareness on these issues among pharmacists and doctors, and therefore errors in interaction with representatives of public organizations, the media or community activists. The aim of the work was the scientific substantiation of the legal and ethical basis of the interaction of pharmacists and doctors with public control subjects of the quality assurance of medicines at the stages of their sale and medical use in Ukraine. To obtain the results of the work, library-semantic, formal-logical and structural-functional methods, methods of comparative legal and technical-legal analysis of legal and ethical, doctrinal and journalistic sources in the chosen direction were used. The work identifies public media control and public monitoring as the forms of public control of the quality assurance of medicines at the stages of their sale and medical use most closely related to the workplaces of pharmacists and doctors. It has been established that the legal basis for the interaction of pharmacists (doctors) and journalists, as subjects of public media control, is determined by the Constitution of Ukraine, scattered groups of regulatory and protective legislation. The ethical basis of such interaction is determined by generally accepted ethical standards, sources of professional pharmaceutical (medical) ethics, sources of professional ethics of journalists. It has also been established that currently in the current legislation of Ukraine there are no separate or special requirements defining the mechanism of interaction between pharmacists (doctors) and public activists who carry out appropriate public control in the form of public monitoring. It was determined that the concretized methods of lawful and ethical interaction of pharmacists (doctors) with journalists and public activists, as subjects of public control of the quality assurance of medicines at the stages of their sale and medical use, require further research. The paper proposed promising areas for improving the legal and ethical mechanisms for realization public control of the quality assurance of medicines at the stages of their sale and medical use by creating a special legislative and ethical-regulatory basis for this type of activity; introducing specialized training in mastering relevant legal and ethical competences for pharmacists (doctors) and for public controllers, which can be either pharmacists (doctors) or any other caring person; introduction of the institute of public inspections to the quality assurance of medicines at the indicated stages of their life cycle, carried out by public inspectors who have passed the specified training.